Numerical studies on the behaviour of intermediate length cold formed steel lipped channel compression members - Marimuthu, V.; Saravanan, M.; Prabha, P.; Sabareshwaran, S.; Jayachandran, S. Arul (Journal of Structural Engineering, 2024)
Usage of cold formed steel structural components for building constructions in India is picking up. Their usage in preengineered buildings is on the high. Being thin members, they are prone to buckling especially under compression. The behaviour of short compression members is well defined in the literature. But the works on the behaviour of intermediate/long compression members is limited. The Indian code IS 801-1975, does not consider the distortional mode of buckling failure and is under revision. Hence, experiments are conducted at CSIR-SERC on intermediate length lipped channel columns to validate the codal provisions. A numerical model is developed to trace the load deformation behaviour obtained from the experiments. This paper presents the details of finite element modeling of two lipped channel columns. Since, the cross sections are very thin and prone to buckling, shell element is used for FE modelling. The length of the column is 2.3 m and the ends are fixed. Static buckling analysis is carried out and buckling modes such as local and distortional are extracted to incorporate the initial imperfections. The over-all imperfection is measured while conducting experiments prior to the load application and is incorporated in the finite element model. Later, static non-linear analysis is carried out with material and geometric non-linearities. The ultimate capacities are predicted and compared.